Casting speed optimal design of 304 stainless steel during twin roll strip casting process by 3D modelling. (October 2014) - Liu, Y. Y.; Liu, L. G.; Guo, J.; Liu, L. L.; Zhang, Y.; Fang, Y.; Yang, Q. X.
Abstract : The exit temperature distribution of 304 stainless steel during twin roll strip casting process was measured. The crack morphology of the actual steel strip was observed by scanning electron microscope. Then, by establishing a three-dimensional model including casting rollers, the flow and temperature fields of 304 stainless steel during the twin roll strip casting process were modelled. The modelled temperature result is in accordance with the measured one, so the flow and temperature fields of 304 stainless steel during the twin roll casting process with different casting speeds can be modelled. The results of the flow field show that a large area of vortex forms in the pool. Those of the temperature field show that the temperature in the vortex zone is lower 30–50°C than that in the refluxing zone, and a thin shell forms on the interface between the molten pool and the casting roller. The whole temperature of the molten pool is increased with the increase in the casting speed, and an optimal casting speed is ∼0·7 m s −1 .